Quem não gosta de samba, bom sujeito não é: consumo e apropriação cultural - Thiago Antonio de Oliveira Sa (2010)
The aims of this work were featuring samba's social ascension, emphasizing the factors that made that musical style become visible and attractive to high and medium classes, and pointing out a seemingly contradictory cultural behavior, that is, those classes' interest in a kind of music made by poor levels of Rio de Janeiro's population. A bibliographic research on samba's History in XX Century Brazil was taken in order to pursuit these two objectives. It's possible to state that samba (1) as a musical preference, isn't a proper representative clue of individuals' social position, because it turned out to be commonplace among classes' consumption; (2) although it was made up by the lowest classes, samba isn't an imitation of dominant culture, but an independent culture-making process; (3) samba inverts the way hierarchically-situated groups pick culture from each other and (4) make symbolic class boundaries unclear, once it contributes for eclectic musical preferences.